Cycling is a lifestyle (if your food is with you): Celiac bicyclists experience’s of cycling - Çeyiz, Senem; Alagül, Özlem (VIREF Revista de Educación Física, 2023)
Objective: The purpose of this study is to learn about the cycling experiences of celiac disease sufferers. Method: In this study, which employs a qualitative research design, in-depth interviews were conducted with five cyclists living in different cities throughout Turkey. The data obtained from the interviews were analyzed through the content analysis method. Results: The study's findings revealed that bicycling individuals have limited freedom due to difficulties in obtaining food and that routine medical examinations take time out of their lives. Meanwhile, it has been observed that they are ignored during bicycle tours due to the fact that they must bring their own food and that such tours do not provide food. They are socially isolated because they are unable to share food with others and have encountered difficulties while participating in cycling tours. Since the gluten-free diet is much more expensive than other foods and they receive no financial assistance, their spending must be restricted to basic necessities. Conclusion: In order for individuals with celiac disease to participate in cycling much more actively, arrangements should be made in social environments that meet the needs of this disease, and political regulations have a negative impact on active cycling.